The Russian invasion of Ukraine: An anti-constitutional moment in international law? - Peters, Anne (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2024)
The Russian invasion of Ukraine was the first open and blatant aggression against a sovereign neighbour state in Europe since 1945. Does this war have systemic significance for the legal order as a whole? The contribution singles out legal trends that relate to three fundamental principles of the current international legal order: peace, people (humanity), and the planet. My thesis is that, although Russia has breached a fundamental, even constitutional, principle of international law, namely the prohibition of inter-state military force, this breach has productively – though unintentionally – boosted, firstly, a modest reform of the UN architecture and, secondly, a further humanization of international law. A third trend is the ‘greening’ of the law surrounding war and of the legal status of the individual. These are important positive developments that go to the very heart of international law. With some optimism, the ‘Ukraine moment’ can therefore be seen not only as an anti-constitutional, but at the same time also as a constitutional moment.